Does Gastrointestinal Dysmotility Predispose to Recurrent or Severe Forms of Clostridium difficile Infections?. (11th December 2014) - Hritani, Abdul wahab; Alkaddour, Ahmad; House, Jeff
Abstract : Clostridium difficile infection (CDI) is the most common cause of hospital-acquired diarrhea. A limited number of studies have looked at the risk factors for recurrent CDI. Mitochondrial NeuroGastroIntestinal Encephalopathy (MNGIE) is a rare multisystemic disorder that causes gastrointestinal dysmotility. Herein we present a patient with MNGIE who suffered recurrent and severe C. difficile infection despite appropriate treatment. We aim to bring the gastroenterologist's attention to gastrointestinal dysmotility as a possible risk factor for the development of recurrent or severe forms of C. difficile infections.